2014
DOI: 10.1371/journal.pone.0108522
|View full text |Cite
|
Sign up to set email alerts
|

Genome Features of the Endophytic Actinobacterium Micromonospora lupini Strain Lupac 08: On the Process of Adaptation to an Endophytic Life Style?

Abstract: Endophytic microorganisms live inside plants for at least part of their life cycle. According to their life strategies, bacterial endophytes can be classified as “obligate” or “facultative”. Reports that members of the genus Micromonospora, Gram-positive Actinobacteria, are normal occupants of nitrogen-fixing nodules has opened up a question as to what is the ecological role of these bacteria in interactions with nitrogen-fixing plants and whether it is in a process of adaptation from a terrestrial to a facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 111 publications
(129 reference statements)
6
84
0
7
Order By: Relevance
“…Further, analysis of the genome of M. lupini Lupac 08 revealed a diverse array of genes that may help the bacterium to survive in the soil or in plant tissues. However, despite having many genes that encode putative plant material-degrading enzymes, this bacterium is not regarded as a plant pathogen (79). In addition, genome comparisons showed that M. lupini Lupac 08 is metabolically closely related to Frankia sp.…”
Section: Molecular Classificationmentioning
confidence: 99%
“…Further, analysis of the genome of M. lupini Lupac 08 revealed a diverse array of genes that may help the bacterium to survive in the soil or in plant tissues. However, despite having many genes that encode putative plant material-degrading enzymes, this bacterium is not regarded as a plant pathogen (79). In addition, genome comparisons showed that M. lupini Lupac 08 is metabolically closely related to Frankia sp.…”
Section: Molecular Classificationmentioning
confidence: 99%
“…The use of the reverse complementary probe of EUB338 (NONEUB) as a negative control (19, figure 3g), (63, figure 4a) is not helpful in this respect because plant organelles are not targeted by this sense probe. Also, the absence of CARD-FISH signals in microbe-free, axenically grown plants after hybridization with EUB338 (19, supplementary figure 17) is problematic as a negative control because there is ample evidence that plant-associated microbes have the capacity to structurally modify plant tissues, e.g., by cell wall loosening (14,103,106), which would impact probe penetration.…”
Section: A Quest For Improved Cultivation-independent Techniques To Amentioning
confidence: 99%
“…The number of rRNAs and tRNAs in the LU2 strain is comparable with that of other strains listed in Table 1 and may indicate positive selection. A large number of rRNA genes is associated with a high activity of the translational apparatus, which in turn increases both the protein synthesis rate and the growth rate 19 . This phenomenon may be connected with strong competition among microorganisms located in the same ecological niche.…”
mentioning
confidence: 99%